Deep into Pharo - Bergel, Alexandre; Cassou, Damien; Ducasse, Stéphane; Laval, Jannik; Open Textbook Library (Open Textbook Library, 2013)
Pharo is a clean, innovative, open-source, live-programming environment. Deep into Pharois the second volume of a series of books covering Pharo. Whereas the first volume is intended for newcomers, this second volume covers deeper topics.You will learn about Pharo frameworks and libraries such as Glamour, PetitParser, Roassal, FileSystem, Regex, and Socket. You will explore the language with chapters on exceptions, blocks, small integers, and floats. You will discover tools such as profilers, Metacello and Gofer.
1 Preface -- I Libraries -- 2 Zero Configuration Scripts and Command-Line Handlers -- 3 Files with FileSystem -- 4 Sockets -- 5 The Settings Framework -- 6 Regular Expressions in Pharo -- II Source Management -- 7 Versioning Your Code with Monticello -- 8 Gofer: Scripting Package Loading -- 9 Managing Projects with Metacello -- III Frameworks -- 10 Glamour -- 11 Agile Visualization with Roassal -- 12 Scripting Visualizations with Mondrian -- IV Language -- 13 Handling Exceptions 263 -- 14 Blocks: a Detailed Analysis -- 15 Exploring Little Numbers -- 16 Fun with Floats -- V Tools -- 17 Profiling Applications -- 18 PetitParser: Building Modular Parsers -- --
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks